Dendritic cell-targeted CD40 DNA vaccine suppresses Th17 and ameliorates progression of experimental autoimmune glomerulonephritis. Issue 4 (27th February 2019) - Li, Qing; Cao, Qi; Wang, Chengshi; Nguyen, Hanh; Wang, Xin Maggie; Zheng, Guoping; Wang, Yuan Min; Hu, Shilian; Alexander, Stephen I; Harris, David C H; Wang, Yiping
Abstract: The CD40-CD40L costimulatory pathway is critical for T cell activation in autoimmune disease. We have previously found that blocking the CD40-CD40L pathway using a dendritic cell-targeted CD40 DNA (DEC-CD40) vaccine prevented the development of Heymann nephritis. In this study, we explored the effect of a DEC-CD40 vaccine in the treatment of experimental autoimmune glomerulonephritis (EAG), an animal model of human Goodpasture's disease induced by antigen α3IV-NC1. DEC-CD40 vaccine given at week 3 and week 6 after 3IV-NC1 injection reduced kidney structural and functional injury significantly in EAG. DEC-CD40 vaccination suppressed Th17 cell numbers and Th17 immune responses in kidney and spleen, but did not alter Th1 cells number and responses. Serum derived from rats with DEC-CD40 vaccination suppressed Th17 differentiation, but not Th1 differentiation in vitro. Furthermore, B cell activation, driven by Th17 cytokines, was suppressed by serum from rats vaccinated with DEC-CD40. A DNA vaccine encoding CD40 and targeting dendritic cell, ameliorates kidney injury in both early and late stages in EAG rats, indicating DEC-CD40 vaccination has a therapeutic role in EAG. Its effect is associated with the reduction of Th17 differentiation and Th17-mediated B cell activation. Graphical Abstract: DEC-CD40 vaccination has a therapeutic role in experimental autoimmune glomerulonephritis, which is associated with the reduction of Th17 differentiation and Th17-mediated B cell activation.